Legal issues of the law regarding the Malaysian citizenship: a comparative study with the United States of America. / Nur' Atiqah Nasir … [et al.] - Nasir, Nur' Atiqah; Mustafa Kamal, Nurul Ainni; Mohd Fauzi, Nurul Afiqah; Jamil, Muhamad Yazid; Abd Ghani, Nur Nina Syarfa' (2013)
This project involves discovering the weaknesses and loopholes in the Malaysian citizenship. The goal is to show that citizenship matters in Malaysia have weaknesses and loopholes regarding the procedure and substantive matters. This has been done by examining the existing laws and rules regarding citizenship in Malaysia and comparing it with the way the law operates in the United States of America and other countries. We also use interviews in written form to validate our research. We use books, journals, legal articles and related acts as our primary sources to strengthen our dissertation. By identifying the problems that arises from the weaknesses and loopholes in the procedural and substantial complications, we will help to improve the citizenship law in Malaysia. This will allow the law to be more efficient both in theoretical and practical ways.